2011
DOI: 10.1017/s1431927611000250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Roughness and Surface Hardness of a Dental Composite Using Atomic Force Microscopy and Microhardness Testing

Abstract: The objective of this study was to evaluate the influence of a cola soft drink (CSD) and coffee on the microhardness and surface roughness of composite resin. Fifty cavities were prepared on the vestibular surface of bovine incisors and restored with nanoparticulate resin. The teeth were divided into five groups (n = 10): group A (control), immersion in artificial saliva (AS) for 14 days; group B, immersion in coffee for 15 min (3×/day) for 7 days followed by immersion in AS for another 7 days; group C, immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Furthermore, chemical softening may have a negative effect on wear and abrasion decreasing the life span of these restorations 8) . The surface roughness analysis was performed by AFM that has been suggested as a accurate method to determine the quality of surface composites 11,15) . The surface roughness of composite resins evaluated (Durafill, Z250 and Z350 XT) increased significantly in 30 days of samples immersion in beer and whisky, except for Durafill and Z250 immersed in vodka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chemical softening may have a negative effect on wear and abrasion decreasing the life span of these restorations 8) . The surface roughness analysis was performed by AFM that has been suggested as a accurate method to determine the quality of surface composites 11,15) . The surface roughness of composite resins evaluated (Durafill, Z250 and Z350 XT) increased significantly in 30 days of samples immersion in beer and whisky, except for Durafill and Z250 immersed in vodka.…”
Section: Discussionmentioning
confidence: 99%
“…For each specimen five indentations were performed under a load of 50 g for 15 s. The Knoop Hardness number (KHN, kg/mm 2 ) for Means followed by distinct capital letters in the same line, and small letters in the same column, are significantly different (p<0.05). each specimen was recorded as the average of the five readings 13,15) .…”
Section: Microhardness Evaluationmentioning
confidence: 99%
“…Published studies have shown that this method may cause tooth and composite abrasion. This degradation process may lead to several drawbacks, such as an increase in wear and surface roughness, softening and a decrease in the hardness of dental materials [3][4][5] . Over time, intraoral degradation also interferes with the fracture strength of the material, culminating in a lower durability of the restoration in the long term 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The durability of restorative materials in the oral cavity is related to their resistance to dissolution and disintegration [1][2][3][4] . Resin composites are frequently subjected to harm in the oral cavity in the form of abrasion (brushing), attrition (diet and parafunctional habits) and erosion (citrus drinks, fruit, soft drinks) [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The erosive activity of beverages affects the composite restorations, leaving a rough surface that influences the optical properties of the material [8][9] , and facilitates the buildup of bacterial plaque and degradation of the surface of the restoration [10][11] . Erosion leads to a reduction in hardness and wear resistance [1][2][3][4] . Moreover, surface roughness can cause gingival irritation and increases the risk of secondary caries 8,10 .…”
Section: Introductionmentioning
confidence: 99%